Settlement Of Marital Disputes Efficacy Through Mediation In The Manado Religious Court - Rosdalina Bukido; Irwansyah Irwansyah; Juliet Ningrum Irawan; Misbahul Munir Makka (Jurnal IUS Kajian Hukum dan Keadilan, 2019)
This study discusses the procedure of divorce settlement through mediation in the Manado Religious Court. These study aims are to know the Procedure of Mediation in the Manado Religious Court and to analyze the Effectiveness of Mediation in the Manado Religious Court. This study was juridical empirical research or sociological legal research. It was qualitative research with the type of descriptive research by using the inductive method of thinking and analyze descriptively. This study used the legislative approach, case approach, sociological approach, and conceptual approach. The results show that determination by Mediator in the Manado Religious Court shall not only be determined by the judges but given the opportunity to the parties to make a selection. Mediation of the marital case in Manado Religious Court has not run effectively. This can be perceptible that the mediation outcomes have decreased every year. In 2015, there were 106 cases which are 6 cases that were successfully mediated. In 2016, there were 94 cases that only 3 cases were successfully mediated. Last in 2017, there were 76 cases, which is only 1 case that was successfully mediated.